CD73 Is Enriched in Cutaneous Carcinomas That Invade the Orbit. Issue 3 (May 2020) - Wladis, Edward J.; Weller, Brandon; Adam, Alejandro P.
Abstract : Purpose: To compare the expression of CD73 in indolent nodular basal cell carcinomas and cutaneous lesions that invade the orbit. Methods: Immunohistochemical staining for CD73 was performed on nodular basal cell carcinomas and invasive basal cell carcinomas. The numbers of positively staining cells were counted across 5 consecutive ×40 microscopic fields, and a statistical comparison was performed via a dedicated computerized software package. Results: Ten control specimens and 11 invasive tumors were analyzed. In nodular basal cell carcinomas, the mean number of positively staining cells was 0.72/×40 field (standard deviation = 0.80 cells/×40 field), whereas invasive tumors demonstrated a mean of 6.53 positive staining cells/×40 field (standard deviation = 3.33 cells/×40 field). This difference was statistically significant ( p = 0.0002). Conclusions: CD73 is enriched in orbital invasion of cutaneous carcinomas. This checkpoint may represent an important target for therapeutic management of these lesions. Immunotherapeutic agents that have been designed to treat other neoplasms may decrease the requirement for orbital exenteration in this clinical scenario. Abstract : CD73 is enriched in orbital invasion of basal cell carcinomas, suggesting that immunomodulation may be an important therapeutic approach to treat this ailment.